Pharmacognostic and Phytochemical Features of Andrographis echioides Whole Plant Powder: Life Sciences-Microbiology - G, Subhashini; K, Chitra Devi; S. K, Sundar; S, Rajan (International Journal of Life Science and Pharma Research, 2022)
Andrographis echioides is one of the stress tolerant plant that belongs to the family Acanthaceae commonly called as Kopuramthangi in Tamil, commonly found in central region of Tamilnadu, India. Local peoples used this plant for fever, to relieve griping, irregular stools and loss of appetite. Indian siddha and ayurvedic pharmacopeia provide standardization criteria for herbal drugs. The aim of the study is to provide quality standards for the powder drug from the whole plant of Andrographis echioides. In order to provide herbal standards for this plant, the present study was undertaken with the objectives to assess pharmacognostic, physiochemical and phytochemical markers of the drug powder of Andrographis echioides whole plant. Andrographis echioides whole plant was collected, authenticated and processed for all pharmacognostic activity using standard textual methods. Powder analysis showed the presence of calcium oxalate crystals, trichomes, fibres, vessel elements and parenchyma cells. The powder is yellowish green in colour with 3.6% ash value with higher water extractive (19.4%). Powder contains a smaller number of microbial flora and no pathogens detected. Multiple fluorochromes were detected in fluorescence test. The pharmacognostic results were within the limits of ayurvedic pharmacopeia of India. Whole plant powder showed the presence of terpenoids, flavonoids, Saponins, phenolic compounds and carbohydrates which could be responsible for all biological activities of the plant. Histochemical analysis also confirmed the availability of phytoconstituents like flavonoids and tannins. The observations made through this study would be of immense value in the pharmacological evaluation and standardization of crude powder of the plant materials.